Design and development of lab model of piezo-optic sensor for Structural Health Monitoring. (21st September 2017) - Sikarwar, Samiksha; Singh, Shakti; Satyendra,; Srivastava, Richa; Yadav, B C; Tyagi, V V
Abstract: This work deals with fibre optic pressure sensors for Structural Health Monitoring (SHM) based on the piezo-optic principle. Various samples were prepared and investigated under room ambient conditions. In one of the samples, periodic microbends of 1 cm spatial periodicity were introduced in the PCS600 optical fibre, which was then embedded in an Araldite matrix with the composition of 60% hardener and 40% resin. This sample was marked as S1 . In another sample, the same fibre without microbending was embedded in the same Araldite matrix, and was marked as S2 . In another sample, the fibre without microbending was embedded in a cement matrix composite, and was marked as S3 . Sample S3 was an effort to develop a pressure sensor for real working environment. Here conventional portland cement was used for the fabrication of the sample. High pressure up to 60 KPa was applied to the sample under cyclic loading and unloading, and the corresponding output power noted. Sensitivities of fibre optic pressure sensor for samples S1, S2 and S3 are 2.304, 0.906 and 2.218 nW KPa –1, with reproducibilities 96.61%, 97.95% and 87.24% respectively. The sensitivities obtained indicate that the sensor has excellent potential to replace existing bulky electrical sensors.